Proceedings of the Conference on Noise Suppression Noise Control 92 - ENGEL, Z. (Archives of Acoustics, 1993)
The IX International Conference on Noise Suppression – NOISE CONTROL 92 was held from the 22-nd to the 24-th September 1992 in Cracow.